Electrocardiographic findings in Anderson-Fabry patients on disease specific therapy: can treatment prevent ECG changes?. (3rd October 2022) - Di Nicola, F; Ditaranto, R; Barlocco, F; Lillo, R; Re, F; Marchi, G; Baldassarre, R; Parisi, V; Ferrara, V; Chiti, C; Gimeno Blanes, J R; Graziani, F; et al.
Abstract: Background: Anderson-Fabry disease (AFD) is an X-linked lysosomal storage disorder that have gained attention due to the availability of therapeutic options. Disease specific therapy (DST), either by enzyme replacement therapy or oral pharmacological chaperone, is the mainstay for AFD treatment. Although its widespread use, few data are available on the electrocardiographic variations associated with DST. Purpose: To evaluate ECG findings and variations in AFD according to time duration of DST, comparing patients under long-term therapy with naïve patients starting therapy during follow-up. Methods: One-hundred-seventy-nine AFD patients, ≥18 years old, with 2 readable ECGs, were recruited in the present multicentre study cohort. Two patients were excluded due to pacemaker (PM) implantation. Only patients on DST (n=107) were considered for final cohort and divided into 2 groups according to therapy duration: Group A (n=42) included patients treated for ≥12 months at the time of first evaluation, whereas Group B patients (n=65) started therapy during follow-up. Results: Group A and Group B had no significant difference in terms of age at presentation (48 [39–60] vs 48 [36–56] years; p=0.856) and maximal wall thickness (13 [11–15] vs 13 [11–18] mm; p=0.090) whereas they differed for male prevalence (61% vs 38%; p=0.029) and classic phenotype (86% vs 29%; p<0.0001). At baseline, more than half of both groups had ECG abnormalities (61% vs 61%; p=1.000). The prevalence among Group A and Group B of atrial fibrillation (AF, 5% vs 6%; p=1.000), first degree atrioventricular block (AVB, 7% vs 5%; p=0.677), right bundle branch block (RBBB, complete 7% vs 8%; p=1.000; incomplete RBBB 14% vs 12%; p=0.776), left anterior fascicular block (LAFB, 10% vs 9%; p=1.000) and repolarization abnormalities (48% vs 38%; p=0.423) was not significantly different. Conversely, left ventricular hypertrophy (LVH) was more prevalent in Group A (64% vs 37%; p=0.010). During the follow-up period (57 [60–28] months for Group A vs 70 (37–85) months for Group B; p=0.152), both groups developed electrocardiographic alterations (38% vs 23%; p=0.127). In particular, in Group A, 4 (10%) patients presented AF, 1 (2%) AVB, 7 (17%) complete or incomplete RBBB, 4 (10%) LAFB, 1 (2%) LVH and 8 (19%) repolarization abnormalities. In Group B, 2 (3%) developed AF, 1 (2%) AVB, 7 (11%) complete or incomplete RBBB, 2 (3%) LVH and 11 (17%) repolarization abnormalities; none developed LAFB. Conclusions: In this AFD cohort, both patients on chronic DST (Group A) and patients who started treatment during follow-up (Group B) developed ECG alterations. ECG changes during the follow-up were more frequent in Group A (38% vs 23%), mainly composed by classic phenotype and male patients, suggesting a prompt start of therapy at an early stage. Funding Acknowledgement: Type of funding sources: None.